A 10 year retrospective cohort study of inpatients with younger‐onset dementia. (16th September 2020) - Loi, Samantha M.; Eratne, Dhamidhu; Goh, Anita M. Y.; Wibawa, Pierre; Farrand, Sarah; Kelso, Wendy; Evans, Andrew; Watson, Rosie; Walterfang, Mark; Velakoulis, Dennis
Abstract: Objectives: Younger‐onset dementia (YOD) refers to a dementia where symptom onset occurs when the patient is less than 65 years of age. YOD is far less common than late‐onset dementia (occurring when patients are over 65 years old) and more challenging to diagnose due to its heterogeneous presentation. There have been relatively few studies describing demographic and diagnostic characteristics of patients with YOD in the community, particularly with follow‐up information. Methods: A retrospective cohort study was performed of inpatients admitted to a tertiary neuropsychiatry service, located in metropolitan Victoria, Australia, from 2009 to 2019. Inpatients with a YOD diagnosis were identified and data regarding diagnosis, demographics and investigations were obtained. Results: There were 849 individual inpatients who were admitted to the service in the 10‐year period and received comprehensive assessment. There were 306 individuals who received a YOD diagnosis, using contemporaneous diagnostic criteria (frequency 36%). The most common diagnoses were Alzheimer's disease (24.2%), frontotemporal dementia (23.1%), Huntington's disease (16.7%) and vascular dementia (7.8%). More than half of these inpatients were followed up and 6.5% had a diagnostic change when reviewed. Conclusions: This study reports on the largest cohort of YOD to date, with diagnostic breakdown similar to previous retrospective file reviews. The neuropsychiatry service is funded to follow‐up its patients, thus allowing re‐assessment and continuity of care. While there are limitations in this study such as the lack of neuropathological outcomes, the findings emphasise the strengths of follow‐up and appropriate service provision for these patients.